2016
DOI: 10.4310/cag.2016.v24.n2.a7
|View full text |Cite
|
Sign up to set email alerts
|

Compact embedded minimal surfaces in $\mathbb{S}^2 \times \mathbb{S}^1$

Abstract: We prove that closed surfaces of all topological types, except for the non-orientable odd-genus ones, can be minimally embedded in S 2 × S 1 (r), for arbitrary radius r. We illustrate it by obtaining some periodic minimal surfaces in S 2 × R via conjugate constructions. The resulting surfaces can be seen as the analogy to the Schwarz P-surface in these homogeneous 3-manifolds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We will focus on the simply connected three-manifold S 2 × R with non-negative Ricci curvature, where we will overtake the problem of determining the possible topological types of compact embedded H-surfaces. Similar problems have been considered in the literature, e.g., Lawson [5] showed that a compact surface can be minimally embedded in the three-sphere S 3 if and only if it is orientable, and the second author extended this result to the larger family of Berger spheres [16]; moreover, the authors and Plehnert [9] showed that a compact surface can be minimally embedded in a Riemannian product S 2 × S 1 (r) if and only if it has even Euler characteristic. Although the only compact minimal surfaces immersed in S 2 × R are the horizontal slices S 2 × {t 0 }, t 0 ∈ R, in the non-compact case Hoffman, Traizet and White [2] proved the existence of embedded minimal surfaces in S 2 × R with two helicoidal ends and arbitrary genus.…”
Section: Introductionmentioning
confidence: 61%
“…We will focus on the simply connected three-manifold S 2 × R with non-negative Ricci curvature, where we will overtake the problem of determining the possible topological types of compact embedded H-surfaces. Similar problems have been considered in the literature, e.g., Lawson [5] showed that a compact surface can be minimally embedded in the three-sphere S 3 if and only if it is orientable, and the second author extended this result to the larger family of Berger spheres [16]; moreover, the authors and Plehnert [9] showed that a compact surface can be minimally embedded in a Riemannian product S 2 × S 1 (r) if and only if it has even Euler characteristic. Although the only compact minimal surfaces immersed in S 2 × R are the horizontal slices S 2 × {t 0 }, t 0 ∈ R, in the non-compact case Hoffman, Traizet and White [2] proved the existence of embedded minimal surfaces in S 2 × R with two helicoidal ends and arbitrary genus.…”
Section: Introductionmentioning
confidence: 61%
“…In this section we will show existence of some invariant constant mean curvature hypersurfaces by studying the solutions of equation (2), with h a positive constant. Of course the equation is considerably more complicated than equation (8). Moreover the clear description obtained in Theorem 1.1 will not be possible in this case.…”
Section: Proof Of Theorem 11mentioning
confidence: 97%
“…But moreover it follows from the Lemma 2.2 and Lemma 2.3 that the local maxima and minima stay bounded away from π and 0 (respectively). If the values of p at the local extrema also stay bounded away π/2 it is elementary and easy to see from equation (8) that the distance between consecutive extrema of p will have a positive lower bound and therefore p would be defined for all x > z. The only possibility left would be that there exists x 0 > 0 such that lim x→x 0 p(x) = π/2.…”
Section: Proof Of Theorem 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Among those spaces, there are three homogeneous Riemannian manifolds: R 3 , where the classical theory of minimal surfaces has been developed, and S 2 × R and H 2 × R, where many authors have been actively working. Giving a complete list of references on the subject is far from being possible so we will only mention a few of them: Nelli and Rosenberg [12] proved a Jenkins-Serrin-type theorem in H 2 ×R, Hauswirth [6] constructed minimal examples of Riemann type, Sá Earp and Tobiana [18] investigated the screw motion invariant surfaces in H 2 ×R, Daniel [4] and Hauwirth, Sá Earp and Tobiana [7] showed, independently, the existence of an associated family of minimal immersions for simply connected minimal surfaces in S 2 ×R and H 2 ×R, Urbano and the author [20] tackled a general study of minimal surfaces in S 2 × S 2 with applications to S 2 × R, very recently Manzano, Plehnert and the author [9] constructed orientable and non-orientable even Euler characteristic embedded minimal surfaces in the quotient S 2 × S 1 and Martín, Mazzeo and Rogríguez [10] constructed the first examples of complete, properly embedded minimal surfaces in H 2 × R with finite total curvature and positive genus.…”
Section: Introductionmentioning
confidence: 99%